Housing and survival strategies of Basotho: urban women tenants - Muzvidziwa, Victor N. (The Institute of Southern African Studies, 2016)
This paper presents and analyses the gendered experiences of four women tenants in the town of Mafeteng in Lesotho. It draws on a study with a far larger scope than that which is presented here.This in-depth study of tenants, which has produced qualitative data on women's circumstances. The study is framed by gender analytical concepts, and builds upon the experience of the Gender Research on Urbanisation, Planning, Housing and Everyday Life (GRUPHEL) researchers' phase one and two findings. The paper focuses on the women's housing circumstances and housing access as well as their perceptions, hopes, frustrations and survival strategies. A major assumption of the study is that in times of socio-economic crisis women adopt a range of survival strategies to participate actively in shaping their everyday life experiences, but that their space of agency is narrow. However, through what Giddens (1991) calls "practical consciousness" women tenants in Mafeteng managed to cope with life's concerns, in a similar way to what Larsson (1998) observed in Gaborone. A focus on survival strategies contributes to an understanding of women's vulnerability and agency in the context of urban living.